Implementation Of Citizen Data Updating Managent In Order To Educate The Community - Rustomo Rustomo; Yudi Kristanto (The International Journal of Education Management and Sociology, 2022)
Community service is one of the necessities for Higher Education. The next implementation of the Tri Dharma of Higher Education is to carry out Teaching and Research. Implementation of community service by Pertiwi College of Economics Bekasi. Providing understanding and implementation of management and governance of population data for community members in RT 22/08 CKM Bangle Village, Majalaya District, Karawang Regency, West Java. The purpose of implementing population data updating management for community members is to strengthen the duties and functions for community servants entrusted to management, so that valid data is available as a servant of the surrounding community. The art of population data updating is a concept developed using applications to facilitate the collection of population in Bangle Village. The stages of implementing this activity first conduct a survey and needs analysis in order to map the needs and problems that occur in environment, then explore the existing potential and design activities for the need to implement population data management applications. The results of this community service activity are the creation of population data application management with the output of valid and complete citizen profiles and accurate numbering for residents of RT 22/08 Bangle Village.